Process analysis for biphasic dehydration of xylose: effects of solvents on the purification of furfural - An, Jiwon; Lee, Geunjeong; Ha, Jeong Myeong; Park, Myung June (Biofuels, 2022)
A biphasic process for the conversion of the xylose that remains as a by-product after biomass fermentation into furfural was considered to maximize the economics of biomass-based fuel production. Widely used solvents such as toluene and methyl isobutyl ketone are toxic and environmentally unfriendly; therefore, 2-pentanone, which is one of the intermediates of the modeled process in this work, is suggested as an alternative. The amounts of the solvent that allowed 95% of the produced furfural to be recovered were determined, and the required numbers of trays in the solvent recovery column were calculated. In the production of nearly pure furfural, the process with 2-pentanone required a smaller number of trays than that with the other solvents, resulting in the lowest equipment costs and energy usage. In addition, because 2-pentanone can be converted into hydrocarbons during the downstream processes for biofuel production, the required purity for the furfural product in the separation column could be decreased, whereas the other solvents should be fully recovered so that they can be kept within the process. As the purity was decreased, the number of trays needed also decreased, indicating that the economics of the entire process could be improved through lower capital costs.
Keywords: Biofuel production; Biomass-based fuels; Biphasic process; Downstream process; Methyl iso-butyl ketones; Process analysis; Separation column; Solvent recovery; Biomass; biphasic process; furfural; solvent; xylose